Risk-Based Approaches to Business Regulation : A Note for Reformers - Molfetas, Aris; Grava, Lars (World Bank, Washington, DC, 2020)
Governments increasingly use risk-based regulation (RBR) to adapt their degree of regulatory control to the actual risks posed by industry sectors, economic activities, and business establishments. Risk-based regulation aims to protect public goods, such as safety, health, and the environment, while at the same time avoiding unnecessary burdens on businesses. When designing regulation and developing models for monitoring and enforcement, risk guides assessments of costs and benefits. This note presents reformers and practitioners with the highlights of an approach to implementing a risk-based regulation system.